Thermal management system with nanofluids for electric vehicle battery cooling modules. (April 2020) - Wiriyasart, S.; Hommalee, C.; Sirikasemsuk, S.; Prurapark, R.; Naphon, P.
Abstract: Due to higher power density, battery thermal management systems are suitable for cooling battery packages due to maximum temperature has a significant effect on the energy storage, durability, life cycle, and efficiency. Therefore, choosing a proper cooling method for an electric vehicle (EV) battery module to maintain the temperature in the appropriate range is essentially required. This work presents a computational analysis approach to characterize the temperature distribution and pressure drop using nanofluids flowing in the corrugated mini-channel of the EV battery cooling module. The EV battery modules consist of 444 cylindrical lithium-ion cell batteries (18650 type). It is found that the temperature distributions are the most sensitive to the flow direction of coolant, mass flow rate, and coolant types. The best cooling performance of the proposed module (Model II) is obtained with nanofluids as coolant showed 28.65% reduced the maximum temperature as compared with the conventional cooling module (Model I). However, the pressure drop also increases. Besides, the nanofluids as coolant give the cooling capacity higher than that water as a coolant. The present approach from this study can be able to optimize the battery thermal management system for an electric vehicle with an appropriate temperature range.